Dentigerous cyst and the importance of early detection. Report of a pediatric case - Benavides-Guzmán, Olger Jesús (2022)
Dentigerous cysts are a common cystic pathology that develop between the first and third decade of life and are mainly associated with impacted or erupted mandibular third molars followed by maxillary canines and maxillary third molars. These kinds of cysts are the result of the proliferation of enamel epithelium after its formation, the pathogenesis of which is not clear. Few of these cysts have been reported in pediatric patients. The following case report presents the rare occurrence ofa dentigerous cyst in a 6-year-old boy and describes the treatment administered.